Robotic Ultrasonic Measurement of Residual Stress in Complex Curved Surface Components - Qinxue Pan; Chang Shao; Dingguo Xiao; Ruipeng Pan; Xiaohao Liu; Wei Song (Applied Bionics and Biomechanics)
The automatic measurement, especially for products with complex shapes, has always been one of the most important application areas of robots. Aiming at the challenge of measuring residual stress under curved surface, in this paper, the residual stress ultrasonic measuring robot system with two manipulators is constructed, which is based on combining industrial robot technology with residual stress ultrasonic nondestructive measuring technology. The system is mainly composed of a motion control system, an ultrasonic detection system, and a data processing system. The robotic arm controls the movement of the two ultrasonic transducers along the set scanning path which is based on the geometric model of components and adjusts the transducer’s posture in time according to the shape of the workpiece being measured. The configuration information based on workpiece coordinate system is transformed into a position data that takes into consideration the first critical angle and can be recognized by the robot. Considering the effect of curvature, the principle model of residual stress measuring by the critical refraction longitudinal wave is established. The measured signal including the stress state of the measured region, as well as the actual position and posture information of the transducers, is processed by the computer in real time, which realizes automatic nondestructive measurement of residual stress under curved surface.